Lacunary Invariant Statistical Convergence in Fuzzy Normed Spaces - Şeyma Yalvaç (Universal Journal of Mathematics and Applications, 2024)
In the study done here regarding the theory of summability, we introduce some new concepts in fuzzy normed spaces. First, at the beginning of the original part of our study, we define the lacunary invariant statistical convergence. Then, we examine some characteristic features like uniqueness, linearity of this new notion and give its important relation with pre-given concepts.